DEMOGRAPHIC FACTORS INFLUENCING AWARENESS LEVELS OF GOVERNMENT SCHEMES AMONG WOMEN ENTREPRENEURS - Dastidar, Amitabha Ghosh; Singh, Gurdip; Tiwari, Dr. Purnima (ShodhKosh: Journal of Visual and Performing Arts, 2024)
People are the most precious resource this planet has. This explains why his contributions to the economic growth of all nations have been so remarkable. His successful career as an entrepreneur has ensured that his contributions are acknowledged on a worldwide scale. The role of female entrepreneurs in a country's economic growth has recently come to the fore. In an ever-changing world, women are making strides forward. When a woman wants to achieve anything, she may change it into something that suits her goals. This is why the government of India has been implementing a plethora of programs aimed at encouraging women to start their own businesses. These programs entice them with attractive incentives. Government programs that aim to encourage business ownership, especially among women, have a long history of success. Nevertheless, there is a large disparity in the degree of knowledge regarding these schemes when considering demographic variables. The 160 female business owners surveyed provided the main data used in this analysis. The research utilized four distinct government programs aimed toward women. A chi-square test was used to examine the gathered data. In order to empower women and inspire them to start their own enterprises, the study's findings point to the need for more awareness campaigns.